Invent to learn : making, tinkering, and engineering in the classroom - Martinez, Sylvia Libow, ....-; Stager, Gary, ....- (Torrance, Calif. : Constructing Modern Knowledge Press, 2013)
There's a technological and creative revolution underway. Amazing new tools, materials and skills turn us all into makers. Using technology to make, repair or customize the things we need brings engineering, design and computer science to the masses. Fortunately for educators, this maker movement overlaps with the natural inclinations of children and the power of learning by doing. The active learner is at the center of the learning process, amplifying the best traditions of progressive education. This book helps educators bring the exciting opportunities of the maker movement to every classroom.
An insanely brief and incomplete history of making -- Learning -- Thinking about thinking -- What makes a good project? -- Teaching -- Making today -- The game changers -- Stuff -- Shaping the learning environment -- Student leadership -- Make your own maker day -- Making the case -- Do unto ourselves -- Resources to explore.
Keywords: Technological innovations; Teaching - Methodology; Learning